Comparison of the Nasal Release of IL-4, IL-10, IL-17, CCL13/MCP-4, and CCL26/eotaxin-3 in Allergic Rhinitis during Season and after Allergen Challenge. Issue 4 (July 2013) - Baumann, Ralf; Rabaszowski, Matthaeus; Stenin, Igor; Tilgner, Lisa; Scheckenbach, Kathrin; Wiltfang, Jens; Schipper, Joerg; Chaker, Adam; Wagenmann, Martin
Background: Allergic rhinitis is an inflammatory disease characterized by local overproduction of type 2 cytokines and tissue eosinophilia. Recent research suggests the involvement of additional cytokines such as IL-17, chemokine (C-C motif) ligand (CCL) 26/eotaxin-3, and CCL13/monocyte chemoattractant protein-4 (MCP-4) in its pathophysiology. Furthermore, bronchial epithelial cells treated with IL-17 and type 2 cytokines distinctively up-regulated eotaxin-3 gene expression. In this study we investigated the kinetics of IL-4, IL-10, IL-17, eotaxin-3, and MCP-4 in seasonal allergic rhinitis volunteers after nasal allergen challenge (NAC) and their release during natural pollen exposure. Methods: The nasal lavages of 15 symptomatic allergic and 14 nonallergic subjects were collected during the pollination season. Additionally, six allergic subjects underwent a single unilateral nasal allergen and control challenge out of season, and nasal secretions were collected. Levels of IL-4, IL-10, IL-17, eotaxin-3, and MCP-4 in nasal lavages and secretions were measured using an electrochemiluminescent assay. Results: After NAC, allergic subjects had a significant immediate response of nasal symptoms as well as a significant increase at 5 hours of IL-4, IL-10, and IL-17 and at 2, 5, and 24 hours significantly raising levels of eotaxin-3. IL-17 and eotaxin-3 concentrations at 5 hours were correlated (r = 0.94; p = 0.005). During natural pollen exposure, barely detectable levels of IL-17 in allergic subjects were also correlated with eotaxin-3 (r = 0.62; p = 0.01). Eotaxin-3 and MCP-4 levels were significantly elevated 9- or 3.7-fold, respectively, and IL-10 and, unexpectedly, IL-4 were significantly lower in allergic subjects compared with nonallergic subjects. Conclusion: Nasal IL-17, MCP-4, and, possibly, eotaxin-3 may aggravate and IL-10 may alleviate nasal mucosal allergy.